Impact of pneumatic waste removal system on Singapore's solid waste collection - Wang, Yun Fei. (2008)
An overview on the operation of pneumatic refuse conveying system that is used in solid waste management. The key challenge parameters, such as the material proprieties, vertical velocity, pressure drop, attrition problem, the cyclone size, etc, about the pneumatic system were investigated.